Peptide-Based Strategies Against SARS-CoV-2 Attack: An Updated In Silico Perspective - Moroy, G.; Tuffery, P. (Frontiers in Drug Discovery, 2022)
Because of its scale and suddenness, the SARS-CoV-2 pandemic has created an unprecedented challenge in terms of drug development. Apart from being natural candidates for vaccine design, peptides are a class of compounds well suited to target protein-protein interactions, and peptide drug development benefits from the progress of in silico protocols that have emerged within the last decade. Here, we review the different strategies that have been considered for the development of peptide drugs against SARS-CoV-2. Thanks to progress in experimental structure determination, structural information has rapidly become available for most of the proteins encoded by the virus, easing in silico analyses to develop drugs or vaccines. The repurposing of antiviral/antibacterial peptide drugs has not been successful so far. The most promising results, but not the only ones, have been obtained targeting the interaction between SARS-CoV-2 spike protein and the Angiotensin-Converting Enzyme 2, which triggers cellular infection by the virus and its replication. Within months, structure-based peptide design has identified competing for picomolar candidates for the interaction, proving that the development of peptide drugs targeting protein-protein interactions is maturing. Although no drug specifically designed against SARS-CoV-2 has yet reached the market, lessons from peptide drug development against SARS-CoV-2 suggest that peptide development is now a plausible alternative to small compounds.